Palynology Of The Lower Kalicapung Formation Tlogosari, Central Java - Eko Budi Lelono (Testing Center for Oil and Gas LEMIGAS, 2002)
The palynological investigation focuses on the transition sediment of the Lower Kalipucang Formation which overlies the non-marine lava of the Gabon Formation. Both formations are firmly separated by the unconformity which is indicated by the occurrence of basal conglomerate. The Lower Kalipucang Formation outcrops in a small village called Tlogosari, Central Java. Lithologically, it is characterised by the occurrence of basal conglomerate with the intercalation of thin lignites. This lithology is overlain by 2 meter thick of claystone containing lignite strings and some igneous fragments. The intercalation of thin sandstones, conglomerate and lignites are found within claystone lithology. Four samples from the Lower Kalipucang Formation were selected for laboratory processing. Only two samples collected from the upper part of this formation yield rich palynomorphs. The palynomorph assemblage shows the occurrence of brackish and fresh water floras. Based on the appearance of pollen Florschuetzia meridionalis and F. trilobata, it is predicted that the age of the Lower Kalipucang Formation is Middle Miocene. The high abundance of mangrove taxa (especially in sample number LKP-4) such as Avicenia type, Zonocostites ramonae and Camptostemon indicates a well development of mangrove environment. This assumption is supported by well preservation of large mollusc with excellent ornamentation. This ornamentation must have developed in the environment with low energy such as mangrove.